Mismatch repair deficiency identifies patients with high‐intermediate–risk (HIR) endometrioid endometrial cancer at the highest risk of recurrence: A prognostic biomarker. Issue 3 (18th December 2018) - Backes, Floor J.; Haag, Jennifer; Cosgrove, Casey M.; Suarez, Adrian; Cohn, David E.; Goodfellow, Paul J.
Abstract : Background: The objective of this study was to assess the correlation between mismatch repair (MMR) status, disease recurrence patterns, and recurrence‐free survival (RFS) in patients with high‐intermediate–risk (HIR) endometrioid endometrial cancer (EEC). Methods: A single‐institution chart review for consecutive patients who were diagnosed with ECC between 2007 and 2016 was undertaken. Tumor MMR status was determined for all patients based on reported findings for mutL homolog 1 (MLH1), postmeiotic segregation (PMS2), mutS homolog 2 (MSH2), and MSH6 immunohistochemistry; and defective MMR (dMMR) status was defined as the lack of expression of at least 1 of these proteins. Patients were classified with HIR EEC according to criteria used for Gynecologic Oncology Group study 249. The factors associated with recurrence were assessed by logistic regression. RFS and associated factors were assessed by Kaplan‐Meier survival analysis and Cox proportional‐hazards models. Results: In total, 197 patients who had HIR EEC (64 with dMMR and 133 with intact MMR [iMMR]) were identified, of whom 32 (16.2%) developed recurrent disease. The median follow‐up was 54 months. The recurrence rate for women who had dMMR was 28% compared with 10.5% for those who had iMMR ( P = .002), independent of the type of adjuvant therapy they received. The increase in distant recurrences among patients who had dMMR was even more pronounced (14.1% vs 3%; P = .003). The estimated 5‐year RFS was 66% for women who had dMMR compared with 89% for those who had iMMR ( P = .001). Excluding isolated vaginal recurrences, the difference in 5‐year RFS was 73.5% versus 95%, respectively ( P = .0004). Conclusions: Patients who had HIR EEC with dMMR had increased rates of recurrence and decreased RFS compared with those who had HIR EEC with iMMR, despite the receipt of similar adjuvant treatment. The current findings highlight the need for alternative treatment options and the importance of MMR status as a biomarker for patients with HIR EEC. Abstract : Patients who have high‐intermediate–risk endometrioid endometrial cancer with defective mismatch repair have increased rates of recurrence and decreased recurrence‐free survival compared with those who have high‐intermediate–risk disease with intact mismatch repair, despite the receipt of similar adjuvant treatment.